A Systematic Review of Higher Education Academics' Use of Microblogging for Professional Development: Case of Twitter - Singh Lenandlar (De Gruyter, 2020)
The paper presents a systematic literature review of empirical studies on the use of Twitter by higher education academics for professional development. Using content and thematic analyses, this review addressed four research questions related to study characteristics, theoretical and methodological approaches, and the type of professional development activities engaged. The results show that Twitter has been studied from several perspectives using various methodological approaches. The review revealed several limitations, including the paucity of research addressing gender, cultural and geographic differences. Limited use of theory is also observed. Five themes emerged identifying the ways Twitter was used for professional development: 1) academic backchannel, 2) networking, 3) information and resource sharing, 4) keeping updated, 5) public engagement and social commentary. Overall, the literature review suggests Twitter supports some aspects of professional development. However, several issues remain outstanding and in need of further research, including ethical approaches and practices of researchers related to data collection and use.